Pengaruh Scarcity Marketing dan Potongan Harga Terhadap Keputusan Pembelian Produk Erigo di Kota Medan : Penelitian - Wilmer Nicholas Yabes Abi; Onan Marakali Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the effect of scarcity marketing and price discounts on purchasing decisions of Erigo apparel products in Medan City. A quantitative approach with a causal associative design was employed. Data were collected through a Likert-scale questionnaire distributed to 100 respondents selected using purposive sampling, consisting of Erigo consumers aged at least 17 years who had previously made purchases using limited-time promotions, limited stock offers, and price discounts via the Shopee platform. The data were analyzed using multiple linear regression, preceded by validity testing, reliability testing, and classical assumption tests. The results indicate that scarcity marketing has a positive and significant effect on purchasing decisions. Price discounts also have a positive and significant effect on purchasing decisions. Simultaneously, both independent variables significantly influence purchasing decisions. The coefficient of determination (R²) value of 0.545 indicates that scarcity marketing and price discounts explain 54.5% of the variation in purchasing decisions, while the remaining variation is influenced by other factors outside the research model.